Personalen, brukaren och budgeten En kvalitativ intervjustudie om institutionell komplexitet i hemtjänsten - Lange,Erik (2025)
Swedish home care has long been studied in the light of decades of market-oriented policies. Studies illuminate how the publicly administrated Swedish home care is situated in a precarious position, where logics of the market, the bureaucracy and the prevailing profession must be navigated and consolidated. First-line managers are uniquely positioned as they interact with the street-level bureaucrats daily, while also being on the bottom of the bureaucratic vertical administration, therefore having unique street-level perspectives combined with their role as implementers of laws and regulation. This paper combines street-level bureaucracy and institutional logics theory to investigate how first-line managers navigate the potential cross-pressure in a context defined by logic-pluralism through deep qualitative interviews with first-line home care managers in a Swedish municipality. The analysis shows that the existing logics both shapes how the managers navigate their role as mostly policy implementers and more sporadically policy co-makers while seeing the different logics as both resources and sources of cross-pressure. The analysis also shows that the managers refer to the logic of the market in most situations, which further defines their role as policy implementers rather than co-makers, while detaching themselves from the street-level professionals.
Keywords: Institutional logics; street-level bureaucracy; frontline managers; home care; qualitative interviews